PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION DENGAN BURNOUT SEBAGAI VARIABEL INTERVENING (STUDI PADA KARYAWAN CV. COTO MAROS BERKAH DI KOTA MANADO) - sriSri Rahmayani; Tumbuan, Willem J. F. Alfa.; Pandowo, Merinda H.Ch. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This research is motivated by the high level of employee turnover fluctuations that impact the company's operational stability. The main objective of this study is to analyze the effect of job satisfaction on turnover intention with burnout as a mediating variable. This type of research is quantitative with an associative approach conducted at CV. Coto Maros Berkah, Manado City. The population in this study amounted to 38 employees, and the sampling technique used the census method (saturation sampling) so that all members of the population became respondents. Data collection was carried out through questionnaire distribution and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that job satisfaction has a negative and significant effect on turnover intention and burnout. Conversely, burnout has a positive and significant effect on turnover intention. Another important finding proves that burnout significantly mediates the effect of job satisfaction on turnover intention.